2020
DOI: 10.1186/s40494-020-00425-9
|View full text |Cite
|
Sign up to set email alerts
|

Indian Ocean trade connections: characterization and commercial routes of torpedo jars

Abstract: During the Classical Period (300 BC-400 AD), the Indian Ocean emerged as one of the largest hubs of ancient international trade. For a long period, these contacts were described from a Rome-centric point of view, looking at the connections between Rome and India. However, recent studies have demonstrated that the Roman-Indo connection was only one of the vast medium and short distance trade routes involving numerous regions and populations, exchanging goods and culture. Current archaeological investigations ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 28 publications
(38 reference statements)
2
33
0
2
Order By: Relevance
“…Results showed that all the bitumen samples originated from central/southern Iraq (Hit-Abu Jir), north-west of present-day Baghdad (Connan & Carter, 2007: 178). A similar result was obtained from recent research on sherds from bitumen-lined jars found in Inqitat/ Al Hamr al-Sharqiya 1 and Alagankulam, which concluded the bitumen had a probable Babylonian/southern Iraq source (Lischi et al, 2020: figs 5-7). Lastly, bitumen analyses were conducted by Thomas Van de Velde on samples from firstto second-century CE contexts from Ed-Dur, Dibba and Mleiha (Van de Velde, 2015: 107-112).…”
Section: A M Esopota M I a N Or Igi Nsupporting
confidence: 86%
See 4 more Smart Citations
“…Results showed that all the bitumen samples originated from central/southern Iraq (Hit-Abu Jir), north-west of present-day Baghdad (Connan & Carter, 2007: 178). A similar result was obtained from recent research on sherds from bitumen-lined jars found in Inqitat/ Al Hamr al-Sharqiya 1 and Alagankulam, which concluded the bitumen had a probable Babylonian/southern Iraq source (Lischi et al, 2020: figs 5-7). Lastly, bitumen analyses were conducted by Thomas Van de Velde on samples from firstto second-century CE contexts from Ed-Dur, Dibba and Mleiha (Van de Velde, 2015: 107-112).…”
Section: A M Esopota M I a N Or Igi Nsupporting
confidence: 86%
“…Finally, a group of pre-Sasanian bitumen-lined jars has been highlighted by a recent article comparing fragments of bitumen-lined/torpedo jars found in Inqitat/Al Hamr al-Sharqiya 1, southern Oman, and in Alagankulam, southern India (Lischi et al, 2020). Among the different groups analysed, the so-called Fabric B is characterised by a creamy colour and abundant vegetal temper, and is associated with first-second centuries CE archaeological contexts.…”
Section: Dist R I Bu T Ion I N T H E a R A B -Per Si A N Gu Lf A N D Beyon Dmentioning
confidence: 99%
See 3 more Smart Citations